The Political Transformation of Lybia under Qadhafi - Haghebaert, Bruno (Afrika Focus, 1988)
In the Third World, the function of political leadership is more pivotal than in western countries. The subjective factor of Qadhafi has vital bearing on developments in Libya. There was no historical neccessity for Libya to have developed along the revolutionary path that it has. The formation of the Arab Socialist Union, the Popular Revolution, the creation of the Jamahiriya, the inauguration of the Revolutionary Committee movement and the programme of militarisation - all these issues are a result of Qadhafi's wish to "revolutionarize" Libyan society. His ultimate aim was to eliminate all intermediaries between the people and the political power. In practice, real power remained in the hands of Qadhafi and the Revolutionary Committees . A drastic fall in oil revenues and the arrogance and arbitrariness of Qadhafi1s revolutionary zealots led to growing discontent among the Libyan population. The American raid on Tripoli and Benghazi in April 1986 was meant to precipitate Qadhafi's downfall. But his regime was not overthrown and the Libyan leader proved to be a master of political survival. A (temporary) political and economic liberalisation has boosted his popularity. On the eve of the twentieth anniversary of the Libyan revolution, his position still seems to be secure. KEYWORDS : Qadhafi, Libya, Islamic state